Rational strategies for designing next-generation oncolytic viruses based on transcriptome analysis of tumor cells infected with oncolytic herpes simplex virus-1 - Naeme Javid; Shahriyar Abdoli; Majid Shahbazi; Majid Shahbazi (Frontiers in Oncology)
IntroductionOncolytic herpes simplex viruses (oHSVs) are a type of biotherapeutic utilized in cancer therapy due to their ability to selectively infect and destroy tumor cells without harming healthy cells. We sought to investigate the functional genomic response and altered metabolic pathways of human cancer cells to oHSV-1 infection and to elucidate the influence of these responses on the relationship between the virus and the cancer cells.MethodsTwo datasets containing gene expression profiles of tumor cells infected with oHSV-1 (G207) and non-infected cells from the Gene Expression Omnibus (GEO) database were processed and normalized using the R software. Common differentially expressed genes between datasets were selected to identify hub genes and were further analyzed. Subsequently, the expression of hub genes was verified by real-time polymerase chain reaction (qRT-PCR) in MDA-MB-231 (a breast cancer cell line) infected with oHSV-1 and non-infected cells.ResultsThe results of our data analysis indicated notable disparities in the genes associated with the proteasome pathway between infected and non-infected cells. Our ontology analysis revealed that the proteasome-mediated ubiquitin-dependent protein catabolic process was a significant biological process, with a p-value of 5.8E−21. Additionally, extracellular exosomes and protein binding were identified as significant cellular components and molecular functions, respectively. Common hub genes with degree and maximum neighborhood component (MNC) methods, including PSMD2, PSMD4, PSMA2, PSMD14, PSMD11, PSMC3, PSMC2, PSMD8, and PSMA4, were also identified. Analysis of gene expression by qRT-PCR and differential gene expression revealed that GADD45g genes can be effective genes in the proliferation of oncolytic HSV-1 virus.ConclusionThe transcriptome changes in tumor cells infected by oHSV-1 may be utilized to predict oncolytic efficacy and provide rational strategies for designing next-generation oncolytic viruses.